How do lending relationships affect access to credit and loan conditions in microlending? - Behr, Patrick; Entzian, Annekathrin; Güttler, Andre (Journal of Banking & Finance, 2011)
A key problem facing microlenders is the high level of information asymmetry between them and their borrowers. In this paper, we analyze whether the relationship intensity between microlenders and borrowers helps to overcome existing information asymmetries and how this impacts access to credit and loan contract terms. Using a rich loan-level data set provided by a microlender in Mozambique for the years 2000–2006, we find that access to credit improves and that the loan approval process takes less time when relationships become more intense. Borrowers further profit from a more intense relationship through lower guarantee requirements. All effects are more pronounced the more opaque the borrowers are. These results suggest that longer lending relationships indeed help to reduce information asymmetries and that this is beneficial for microborrowers.